Vapor-Liquid Equilibrium Simulation of Binary and Ternary Mixtures of CH4, C2H4 and iso-C4H10 - 张吕鸿 张晶 孙永利 闫娇 刘玉花 刘萌萌 (Transactions of Tianjin University, 2014)
The vapor-liquid equilibrium（VLE） properties for the binary and ternary mixtures of CH4,C2H4 and isoC4H10 are of great importance in the recovery of ethylene from mixture containing CH4 and C2H4 with iso-C4H10 as solvent.Hence,Gibbs ensemble Monte Carlo（GEMC） simulations were used to estimate vapor-liquid equilibrium for the binary and ternary mixtures of CH4,C2H4 and iso-C4H10 with the united atom potential NERD model.The selected simulation conditions are based on the experiment in the literature.The results of this work were shown to be in satisfactory agreement with available experimental data and predictions of Peng-Robinson equation of state.The structure of simulated liquid phase is also characterized by radial distribution function（RDF）,which contributes to further understanding of the VLE curve of these systems.RDF is not sensitive to the pressure and temperature range.With the increase of pressure or the decrease of temperature,the molecules tend to gather together.